2020
DOI: 10.3389/fphys.2020.00371
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Did Not Affect Central and Peripheral Factors of Performance Fatigability After Submaximal Isometric Exercise

Abstract: Behrens et al. Ischemic Preconditioning and Submaximal Exercise determinants, nor muscle activity, SmO 2 , and perceptual responses during submaximal isometric exercise. However, IPC seemed to have an ergogenic effect in a few subjects, which might have resulted from a lower effort perception during exercise. These findings support the assumption that there are 'responders' and 'non-responders' to IPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
(72 reference statements)
3
8
0
Order By: Relevance
“…Modulation of central mechanisms associated with fatigability such as voluntary activation and presynaptic inhibition [ 14 , 50 ] were not altered by IPC in the current study. This is in accordance with others who showed no effects of a single session of IPC on voluntary activation or H-reflex amplitude of the quadriceps muscles in men, but its effects in women were not evaluated [ 11 , 12 , 51 , 52 ]. Nonetheless, it is suggested that some individuals seem to respond to the IPC technique but others do not [ 10 , 52 , 53 ] and differences in the populations involved, the intensity of contraction and muscles recruited are some factors that may explain the contradictory findings across studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Modulation of central mechanisms associated with fatigability such as voluntary activation and presynaptic inhibition [ 14 , 50 ] were not altered by IPC in the current study. This is in accordance with others who showed no effects of a single session of IPC on voluntary activation or H-reflex amplitude of the quadriceps muscles in men, but its effects in women were not evaluated [ 11 , 12 , 51 , 52 ]. Nonetheless, it is suggested that some individuals seem to respond to the IPC technique but others do not [ 10 , 52 , 53 ] and differences in the populations involved, the intensity of contraction and muscles recruited are some factors that may explain the contradictory findings across studies.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with others who showed no effects of a single session of IPC on voluntary activation or H-reflex amplitude of the quadriceps muscles in men, but its effects in women were not evaluated [ 11 , 12 , 51 , 52 ]. Nonetheless, it is suggested that some individuals seem to respond to the IPC technique but others do not [ 10 , 52 , 53 ] and differences in the populations involved, the intensity of contraction and muscles recruited are some factors that may explain the contradictory findings across studies. For example, physical activity levels were suggested to negatively influence the response to IPC [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, neural pathways are speculated for an end effect through afferent signaling feedback to the brain and then to the target organ (e. g. heart) or by arousing humoral pathways through agents in bloodstream and thus possibly improving O 2 delivery via vasodilatory mechanisms [3,29]. Nevertheless, statements that IPC could mediate physiologic efficiency such as recruitment of additional motor units, enhance muscle deoxygenation and improve skeletal muscle blood flow [1] seems to be refuted based on recent research that have not observed such improvements [5,6]. On the other hand, the training status may play a role in the IPC response [4].…”
Section: Plos Onementioning
confidence: 99%
“…Despite IPC having been extensively tested due its low cost and easy application, mechanisms for these effects on performance are still lacking. There are arguments and evidences questioning the peripheral/local effect of IPC [5,6] pointing a potential placebo effect [2]. In this sense, recent research have demonstrated no IPC effect on peripheral fatigue and neuromuscular function compared to sham IPC (SHAM) after submaximal isometric [5] or all out isokinetic tests [6].…”
Section: Introductionmentioning
confidence: 99%